2018
DOI: 10.1016/j.canlet.2018.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Sabutoclax, pan-active BCL-2 protein family antagonist, overcomes drug resistance and eliminates cancer stem cells in breast cancer

Abstract: Misregulation of BCL-2 family of proteins renders a survival signal to withstand cytotoxic anticancer drugs and is often found in drug resistant cells. The drug resistance phenotype is also associated with an enhancement of cancer stem cell-like (CSC) characteristics. Thus, inhibition of anti-apoptotic BCL-2 family proteins has been proposed as a possible antineoplastic strategy, and BCL-2 inhibitors are currently being clinically trailed in patients with leukemia, lymphoma or non-small cell lung cancer. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 64 publications
1
45
0
Order By: Relevance
“…Furthermore, tagalide A and tagalol A are also found to inhibit the phosphorylation of STAT3 and JAK2 in breast cancer [86]. Additionally, sabutoclax, a pan-active BCL-2 protein family antagonist, is found to inhibit the IL-6/STAT3 pathway and thereby overcome multidrug resistance in breast cancer [85], whereas isoharringtonine (IHT) is found to suppress the STAT3/Nanong pathway to inhibit breast cancer proliferation [91].…”
Section: Compounds Inhibiting the Activation Of Stat3 In Breast Cancermentioning
confidence: 99%
“…Furthermore, tagalide A and tagalol A are also found to inhibit the phosphorylation of STAT3 and JAK2 in breast cancer [86]. Additionally, sabutoclax, a pan-active BCL-2 protein family antagonist, is found to inhibit the IL-6/STAT3 pathway and thereby overcome multidrug resistance in breast cancer [85], whereas isoharringtonine (IHT) is found to suppress the STAT3/Nanong pathway to inhibit breast cancer proliferation [91].…”
Section: Compounds Inhibiting the Activation Of Stat3 In Breast Cancermentioning
confidence: 99%
“…A recent study showed that targeting MCL-1 by either treatment an inhibitor or an siRNA sensitizes gastric, colorectal and pancreatic cancer cells [13,14]. For breast cancer, a variety of studies have shown that there is an identi ed relationship between MCL-1 and resistance [15,16]. However, interestingly, we found that MYC may cooperate with MCL-1 to maintain cancer stem cells (CSCs) [5].…”
Section: Introductionmentioning
confidence: 64%
“…Bax is an important additional contributor affecting the balance of apoptosis [29,30] . We found that treatment with rottlerin increased the level of Bcl-2 in DSS-treated group and decreased the level of Bax.…”
Section: Discussionmentioning
confidence: 99%